Analisis Desain Produk Sereal Froot Loops - Dewi Insanah; Seanyca Putri; Lawrend Friscyliana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Design of a Froot Loops cereal product, with the primary objective of identifying and resolving any problems in the design that may exist. The methods used included visual, sensory and ergonomic evaluation, with data collected from users and related market research. From the analyses, conclusions were drawn that design improvements can enhance the appeal of the product as well as the consumer experience, focusing on aesthetic aspects, consumption convenience, and product sustainability.